Walking Tour as Cultural Tourism: Mlaku 01 Cirebon - Ramiz Ansharil Haq; Ahmad Candra (Haluan Sastra Budaya, 2024)
Cultural history of some places is sometimes difficult to recognize its original culture, one of which is due to transformation of some buildings in the area. Because of that, the origin will be spoiled and forgotten because local cultural shift is an inevitable social phenomenon. Cultural and historical tours through walking tours are one of ways to keep the story of a region unabated. Besides, the benefit of walking tours is also being a positive cultural exchange between local communities and visitors. Cirebon was a small village built by King of Tapa. In the course of time, it grew into a large village and it was named Caruban (means united according to the mixture of nations and other tribes such as Java, Chinese, and Arabic from Javanese Language). The goal of walking tour in context of cultural tourism is to remember, introduce, and promote original culture of an area in Cirebon City.